Optimal Tariff Policy and Endogenous Market Structure - Tito Cordella; Stefano Vannini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1992)
Strategic trade policy affects foreign-based furn's internationalization mode. In this paper, we endogenize market structure and tariff policy by considering a sequential game in which (i) a policy-maker maximizes national welfare, (ii) aforeign-based furn decides whether to supply the host-country market by exports orby activating a local plant, (iii) a local furn decides whether entering or not the domestic market, (in) both Gums choose output. We show that optimal tariff policy does no tallow for the existence of multinational enterprises at equilibrium (when transportation costs are neglected). Tile link between national welfare and fixed costs is fairly complex and counterintuitive results arise.
Keywords: 330